Perubahan Paradigma Dakwah Gen Z Muslim: Preferensi Pendekatan Naratif dan Ekspresi Diri di Media Sosial - Hasbiyah Puan Syafa; Sri Wulandari; Restu Ismoyo Aji (Ad-DA'WAH, 2026)
This study aims to examine the changing paradigm of da'wah among Generation Z (Gen Z) in the context of social media developments and self-expression factors. Da'wah, which previously tended to be formal, one-way, and normative, has now transformed into a more visual, personal, and interactive format. This study used a mixed methods approach through questionnaires, literature studies, and observations of da'wah practices on social media. The results show several key trends, including the dominance of short-form visual content, the use of more communicative and relatable language, and the increase in da'wah practices based on personal experiences such as self-reflection and storytelling. Furthermore, the credibility of a message is no longer solely determined by scientific authority but also by the emotional closeness and authenticity of the deliverer. Social media acts as a catalyst in shaping audience preferences for fast and engaging content. However, this condition also poses challenges in the form of potential simplification of Islamic teachings. Therefore, da'wah needs to be developed creatively, inclusively, and contextually to remain relevant.